Virtual Education for All: Systematic Review (2019)
This article deals with the systematic review of the literature on virtual education for all. Accurately, this work responds to questions such as: What are the technological and pedagogical considerations to implement accessible e-learning proposals in inclusive higher education? What role does the Universal Design for Learning play in the development of virtual educational proposals for all in higher education? Scientific productions were analysed from 2009 to 2018. The study is based on the methodology proposed by Kitchenham (2004) and Okoli & Schabram (2010). The revised productions provide empirical and theoretical data in the field of inclusive virtual higher education. The results show that the accessibility to educational platforms and resources or educational contents has been of great interest, as well as the consideration of the Universal Design for Learning and its three principles to reach the most considerable number of online learners, with training proposals accessible to all who seek an inclusive virtual education.